RGD peptide-modified dendrimer-entrapped gold nanoparticles enable highly efficient and specific gene delivery to stem cells - Kong, Lingdan (2019)
We report the use of arginine-glycine-aspartic (Arg-Gly-Asp, RGD) peptide-modified dendrimer-entrapped gold nanoparticles (Au DENPs) for highly efficient and specific gene delivery to stem cells. In this study, generation 5 poly(amidoamine) dendrimers modified with RGD via a poly(ethylene glycol) (PEG) spacer and with PEG monomethyl ether were used as templates to entrap gold nanoparticles (AuNPs). The native and the RGD-modified PEGylated dendrimers and the respective well characterized Au DENPs were used as vectors to transfect human mesenchymal stem cells (hMSCs) with plasmid DNA (pDNA) carrying both the enhanced green fluorescent protein and the luciferase (pEGFPLuc) reporter genes, as well as pDNA encoding the human bone morphogenetic protein-2 (hBMP-2) gene. We show that all vectors are capable of transfecting the hMSCs with both pDNAs. Gene transfection using pEGFPLuc was demonstrated by quantitative Luc activity assay and qualitative evaluation by fluorescence microscopy. For the transfection with hBMP-2, the gene delivery efficiency was evaluated by monitoring the hBMP-2 concentration and the level of osteogenic differentiation of the hMSCs via alkaline phosphatase activity, osteocalcin secretion, calcium deposition, and von Kossa staining assays. Our results reveal that the stem cell gene delivery efficiency is largely dependent on the composition and the surface functionality of the dendrimer-based vectors. The coexistence of RGD and AuNPs rendered the designed dendrimeric vector with specific stem cell binding ability likely via binding of integrin receptor on the cell surface and improved three-dimensional conformation of dendrimers, which is beneficial for highly efficient and specific stem cell gene delivery applications.